2014
DOI: 10.1542/hpeds.2014-0072
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Recruitment Rates in an Inpatient Clinical Research Study Using Quality Improvement Methods

Abstract: Objective One important benefit of successful patient recruitment is increased generalizability of findings. We sought to optimize enrollment of children admitted with asthma as part of a population-based, prospective, observational cohort study with the goal of enrolling at least 60% of all eligible and staffed patients. Methods Quality improvement methods were used to improve cohort recruitment. Weekly meetings with study staff and study leadership were held to plan and discuss how to maximize recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In evaluating feasibility, we assessed intervention fidelity and enrollment and retention rates, setting a target of 80% for both. While we achieved our target for participant retention, our consent rate was short of our goal but similar to that reported in other studies 32 or reported in trials where consent was obtained from family members 33 . We acknowledge a potential for selection bias, which may have occurred because consenting families may have viewed the intervention positively from the outset.…”
Section: Discussionsupporting
confidence: 57%
“…In evaluating feasibility, we assessed intervention fidelity and enrollment and retention rates, setting a target of 80% for both. While we achieved our target for participant retention, our consent rate was short of our goal but similar to that reported in other studies 32 or reported in trials where consent was obtained from family members 33 . We acknowledge a potential for selection bias, which may have occurred because consenting families may have viewed the intervention positively from the outset.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, recruitment for the study was limited by selection bias. The recruitment rate of 51% for the patient cohort is standard for pediatric clinical research 23 . However, a higher recruitment rate could increase the proportion of participants with other genotypes of SCD, as our study population was biased with a majority of patients with HbSS disease, which would increase the generalizability of the study.…”
Section: Discussionmentioning
confidence: 99%
“…During our efforts to increase referrals to the exiting home visit program, we made iterative changes and used run charts to track progress, methods proven useful in many health care settings, including patient recruitment. 17 We propose that these methods may also have a role in execution of research, including recruitment and follow-up measurement, augmenting previous work that has used run-in periods focused on effectiveness and efficacy. 4 …”
Section: Discussionmentioning
confidence: 99%